A DISCUSSION ON THE STIFFNESS MATRICES USED IN TENSEGRITY STRUCTURES - Gil-Martin, Luisa María; Fernandez-Ruiz, Manuel Alejandro; Hernandez-Montes, Enrique (Journal of Applied Engineering Science, 2017)
The expression stiffness matrices used in the study of tensegrity structures has inherited a formulation initially conceived for the shape finding problems of tension structures. Nevertheless stiffness and geometrical stiffness matrices are well known concepts of structural analysis and all the formulations which are used need to be congruent.  In this paper, we present a formal discussion about the formulations used in several publications showing that they are not equivalent. A classic example is presented, which has been solved using several expressions available in the relevant literature, the results have been compared with a classical finite element software, showing the discrepancies.